Novel phenotyping method to assess the glycemic index (GI) of cooked rice samples - CGIAR Research Program on Rice (2020)
The superior haplotype defined for lowering GI were scanned in 94 breeding lines and identified two low to intermediate GI breeding lines (IRRI 162 and IRRI 163) and confirmed its in vivo GI values were in the range of 57 and 64, respectively.